Neuroregulation in Esophageal Cancer: Unveiling the Role of Neural Pathways in Tumor Progression and Therapy Optimization - Leão, Larissa Medeiros Maia; Meneses Rêgo, Amalia Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2025)
Esophageal cancer (EC) remains a highly lethal malignancy with limited therapeutic success and poor survival rates despite advances in surgical and systemic treatments. Recent insights into the intricate interplay between the nervous system and tumor biology have revealed the critical role of neural pathways in shaping the tumor microenvironment (TME). These interactions influence tumor progression, metastasis, and resistance to therapy, positioning neural regulation as a promising yet underexplored area in EC research. Neurotransmitter agents and neurotrophic factors actively modulate key processes, including angiogenesis, immune evasion, and cellular plasticity, while also contributing to therapeutic resistance. Additionally, identifying tumor biomarkers related to neural activity offers new possibilities for early detection and personalized treatment strategies. This review synthesizes current evidence on the contributions of nervous system physiological phenomena to EC, exploring the mechanisms by which neural signaling interacts with immune modulation and TME. By examining the dual roles of neural regulation in promoting tumor aggressiveness and mediating therapeutic outcomes, the review highlights the potential for targeting these pathways to improve clinical management. Furthermore, gaps in the current literature, such as the variability of findings across tumor subtypes and the lack of standardized methods for assessing neural involvement, are critically discussed. Future directions emphasize the integration of neural-targeted therapies with existing modalities and developing biomarkers to optimize patient outcomes. This review underscores the importance of a multidisciplinary approach in advancing our understanding of EC and addressing its clinical challenges.